2018
DOI: 10.1007/s13224-018-1162-0
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Pregnancy and Its Danger Signs Not Improved by Maternal and Child Health Handbook

Abstract: Background High numbers of maternal mortality rate and child mortality rate continue to be the pressing issues in Indonesia. To tackle this problem, multiple approaches have been undertaken, particularly through distributing a Maternal and Child Health (MCH) handbook to every pregnant woman. However, despite the widespread usage of such handbook, its true efficacy in supporting safe motherhood by improving maternal knowledge on various stages of pregnancy and the associated obstetric danger signs is relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 12 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…Meanwhile, another study in Indonesia about the effects of the Maternal and Child Health Handbook on improving knowledge of the pregnancy danger signs found contradictory results. It was concluded that the Maternal and Child Health Handbook could not improve knowledge of the pregnancy danger signs [31].…”
Section: Plos Onementioning
confidence: 99%
“…Meanwhile, another study in Indonesia about the effects of the Maternal and Child Health Handbook on improving knowledge of the pregnancy danger signs found contradictory results. It was concluded that the Maternal and Child Health Handbook could not improve knowledge of the pregnancy danger signs [31].…”
Section: Plos Onementioning
confidence: 99%
“…Two were randomised controlled trials [ 21 , 22 ]; three cluster randomised trials [ 23 25 ] and one reporting three year follow-up results of a cluster randomised trial [ 26 ]; eight pre-post studies [ 27 34 ]; 25 cross sectional studies [ 35 59 ]; two qualitative studies [ 60 , 61 ] and one mixed method study [ 62 ]. Sixteen countries; Bangladesh (n = 2) [ 28 , 59 ]; Brazil (n = 10) [ 45 , 49 , 50 , 53 – 57 , 60 , 61 ]; Burkina Faso(n = 1) [ 44 ]; Burundi (n = 1) [ 30 ]; Cambodia (n = 1) [ 31 ]; The Gambia (n = 1) [ 62 ];Indonesia (n = 7) [ 23 , 25 , 34 , 36 , 46 , 47 , 52 ]; Kenya (n = 3) [ 39 , 40 , 48 ]; Lebanon(n = 1) [ 43 ]; Malawi(n = 1) [ 58 ]; Mongolia(n = 3) [ 24 , 26 , 35 ]; Nigeria (n = 1) [ 51 ];Pakistan(n = 2) [ 21 , 22 ]; Palestine(n = 2) [ 29 , 37 ]; South Africa (n = 4) [ 32 , 38 , 41 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies [ 23 , 24 , 27 29 , 34 , 46 ] evaluated the use of HBR and its effects on knowledge, attitude, and practice outcomes. One study did not report any improvement in knowledge after the use of HBR [ 46 ]. Individual study results can be found in Table 5 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of novel early detection of high-risk pregnancy can be one solution in answering several weaknesses of government programs, including the safe motherhood program where there are still several areas in Indonesia with difficult access to healthy childbirth, the causes can be in the form of geographic reasons and equal distribution of health workers [18], [19]. Apart from that, good and regular antenatal care services do not yet cover all areas of Indonesia in the overall geographic topography, even though one of the specific health problems of pregnant women is antenatal care through antenatal services.…”
Section: Discussionmentioning
confidence: 99%